Measurement of Calorie from Image of an Apple - Bhaskar, Lavanya; Lathika, (International Journal of Computer Sciences and Engineering, 2019)
Nowadays, every individual has become health-conscious and wants to be protected against diseases. Everyone wants to eat a balanced diet and also keep a track of the daily calorie intake. This work in the image processing domain serves this purpose as it determines the calorie content from the image itself. For the purpose of calorie calculation, an image of the food sample is required. Initially, a person captures an image of apple; which is later processed in MATLAB. One of the key requirements of this work is that the images be taken at a constant distance of 25-35 cms from the apple. The different varieties of apples that are taken into consideration are: dark red, lighter red and one with red with yellowish parts. In the pre-processing stage, this image is read and converted into gray. Later, at the segmentation stage, the image is analyzed using K means clustering algorithm to extract the image of apples. After this, the feature extraction process takes place, which includes extraction of features like color, shape, size, weight and texture. The determination of weight is undertaken by calculating the number of pixels. Next, in the classification step, SVM classifier is used in which, the apple will be analyzed using some nutritional tables and the calorie value will be displayed to the person.